2010
DOI: 10.1111/j.1365-2362.2010.02430.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylcobalamin effects on diabetic neuropathy and nerve protein kinase C in rats

Abstract: This study suggested that correction of impaired neural signalling of PKC and oxidative stress-induced damage may be a major attribute to the beneficial effects of MC on diabetic nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
(65 reference statements)
3
28
0
2
Order By: Relevance
“…Furthermore, experimental studies in streptozotocin-diabetic rats [83, 84] and a small open-label clinical trial [85] with another niacin derivative, niceritrol, demonstrated reduction of serum triglyceride concentration and alleviation of peripheral neuropathy, in the absence of amelioration of diabetic hyperglycemia. This apparent similarity of action between niacin (vitamin B3)/its derivatives and other B vitamins is not surprising because niacin [85], its derivative acipimox in the current study, and other afore-mentioned B vitamins [82, 86, 87] counteract oxidative-nitrosative stress. Note, however, that only niacin and its derivatives, but not other B vitamins, display potent hypolipidemic activity.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Furthermore, experimental studies in streptozotocin-diabetic rats [83, 84] and a small open-label clinical trial [85] with another niacin derivative, niceritrol, demonstrated reduction of serum triglyceride concentration and alleviation of peripheral neuropathy, in the absence of amelioration of diabetic hyperglycemia. This apparent similarity of action between niacin (vitamin B3)/its derivatives and other B vitamins is not surprising because niacin [85], its derivative acipimox in the current study, and other afore-mentioned B vitamins [82, 86, 87] counteract oxidative-nitrosative stress. Note, however, that only niacin and its derivatives, but not other B vitamins, display potent hypolipidemic activity.…”
Section: Discussionsupporting
confidence: 51%
“…In previous studies, several B vitamins i.e., thiamine (B 1 ), pyridoxine (B 6 ), and methylcobalamin (B 12 ), ameliorated diabetes-induced peripheral nerve dysfunction [8082]. Furthermore, experimental studies in streptozotocin-diabetic rats [83, 84] and a small open-label clinical trial [85] with another niacin derivative, niceritrol, demonstrated reduction of serum triglyceride concentration and alleviation of peripheral neuropathy, in the absence of amelioration of diabetic hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…As all know that the pathogenesis of DPN has been caused by a number of metabolic abnormalities including polyol pathway hyperactivity, increased advanced glycation end-point formation, alterations in the protein kinase C pathway and reduced supply of neurotrophic factors (Dobrowsky et al, 2005;Mizukami et al, 2011;Obrosova et al, 2007;Song et al, 2003). In particular, aldose reductase, the first enzyme in the polyol pathway, is localized in Schwann cells in the peripheral nervous system (Kern and Engerman, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Methylcobalamin effects on diabetic neuropathy and nerve protein kinase C (PKC) in rats [52] (Soroku Yagihashi and Hiroki Mizukami)…”
Section: Hormonal and Plasma Volume Changes After Presyncope [51] (Hementioning
confidence: 99%